Failure analysis of driveshaft of Toyota SEG - Shuhaizal, Mohd Noor (2007)
Power transmission system of vehicles consist several components which sometimes encounter unfortunate failures. Some common reasons for the failures may be manufacturing and design faults, maintenance faults raw material faults, material processing faults as well as the user originated faults. In this study, fracture analysis of a drive shaft of an automobile power transmission system is carried out. Hardness measurements are carried out for each part. For the determination of stress conditions at the failed section, stress analyses are also carried out by the finite element (ALGOR) method. The fatigue test experiment had been done to see how long the drive shaft can be stay before had any failure. By compare the hardness number and the properties of material, the driveshaft is make from medium carbon steel. It has higher endurance limit compare to mild steel, brass and aluminum (pure).